World Seas: An Environmental Evaluation Volume III: Ecological Issues and Environmental Impacts - Hamel, Jean-Francois; Hamel, Jean-Francois (Academic Press, 2018)
World Seas: An Environmental Evaluation, Second Edition, Volume Three: Ecological Issues and Environmental Impacts covers global issues relating to our seas, including a biological description of the coast and continental shelf waters, the development and use of the coast, landfills and their effects, pollutant discharges over time, the effects of over-fishing, and the management methods and techniques used to ensure continued ecosystem functioning. The relative importance of water-borne and airborne routes differ in different parts of the world is explored, along with extensive coverage of major habitats and species groups, governmental, education and legal issues, fisheries effects, remote sensing, climate change and management. This book is an invaluable, worldwide reference source for students and researchers concerned with marine environmental science, fisheries, oceanography and engineering and coastal zone development. - Provides scientific reviews of regional issues, empowering managers and policymakers to make progress in under-resourced countries and regions - Covers environmental issues arising from the human use of both the sea and its watershed - Presents informed commentary on major trends, problems and successes, and recommendations for the future